Análise numérica de estruturas de aço, concreto e mistas em situação de incêndio - Rodrigo Barreto Caldas (2008)
This work presents the development and implementation of nonlinear numerical models for the thermal and mechanical analyses of steel, reinforced concrete and composite structures of steel and concrete subjected to fire. Heat transfer procedures, based on finite differences and finite elements at the cross section level, provide the temperaturedistribution from which the material degradation under fire may be assessed. A new procedure for the strength analysis of arbitrary cross sections of beam, columns and slabs under fire is presented. Three-dimensional beam-column element, able to simulate framed structures under fire action, are implemented and tested. To simulate reinforced concrete slabs under high temperatures, a layered shell finite element with a damage constitutive model is introduced. Finally, a spring element for semi-rigid connections under fire action is developed and coupled to the beam-column elements. The numerical schemes are validated by comparison with numerical and experimental results found in the literature.